(untitled) (SAARC Journal of Agriculture, 2024)
The study was conducted in the research field of Sher-e Bangla Agricultural University, Dhaka, Bangladesh from November 2020 to February 2021 to characterize seven Brassica rapa and their 42 F1 genotypes for morphological traits. Most of the F1s showed intermediate characteristics between their parents for leaf, flower and pod characters. The parent, Brown Special matured within the shortest time (80.66 days) with moderate yield (5.88g plant-1). All the F1s had higher yield potential than their parents, except BARI Sharisha-15×BARI Sharisha -14 and BARI Sharisha-15×BARI Sharisha-17. The F1 (Tori-7×Brown Special) matured within the shortest time (80.00 days) with yield of 13.24g plant-1. The F1s (Brown Special×BARI Sharisha-14), (Yellow Special×Brown Special), (BARI Sharisha-14×Tori-7), (Brown Special×BARI Sharisha-15) matured in 82.00, 83.00, 83.00 and 85.00 days, respectively with yield 11.59, 15.79, 13.27 and 26.02 g plant-1, respectively. While the F1s, (BARI Sharisha-15×Brown Special) and (Tori-7×Yellow Special) matured in late, 92.88 and 96.00 days, respectively, but had very high yield potential of 22.34 and 27.67 g plant-1, respectively. Therefore, these genotypes possessed excellent potential for use in future trial. SAARC J. Agric., 22(1): 139-152 (2024)